Genomic changes underpinning the emergence of a successful Mycobacterium tuberculosis Latin American and Mediterranean clonal complex - Dekhil, Naira; Mardassi, Helmi (Frontiers in Microbiology, 2023)
The Latin American and Mediterranean sublineage (L4.3/LAM) is the most common generalist sublineage of Mycobacterium tuberculosis lineage 4 (L4), yet certain L4.3/LAM genotypes appear to be confined to particular geographic regions. This is typically the case of a L4.3/LAM clonal complex (CC), TUN4.3_CC1, which is the most preponderant in Tunisia (61.5% of L4.3/LAM). Here, we used whole-genome sequencing data of 346 globally distributed L4 clinical strains, including 278 L4.3/LAM isolates, to reconstruct the evolutionary history of TUN4.3_CC1 and delineate critical genomic changes underpinning its success. Phylogenomic coupled to phylogeographic analyses indicated that TUN4.3_CC1 has evolved locally, being confined mainly to North Africa. Maximum likelihood analyses using the site and branch-site models of the PAML package disclosed strong evidence of positive selection in the gene category “cell wall and cell processes” of TUN4.3_CC1. Collectively, the data indicate that TUN4.3_CC1 has inherited several mutations, which could have potentially contributed to its evolutionary success. Of particular interest are amino acid replacements at the esxK and eccC2 genes of the ESX/Type VII secretion system, which were found to be specific to TUN4.3_CC1, being common to almost all isolates. Because of its homoplastic nature, the esxK mutation could potentially have endowed TUN4.3_CC1 with a selective advantage. Moreover, we noticed the occurrence of additional, previously described homoplasic nonsense mutations in ponA1 and Rv0197. The mutation in the latter gene, a putative oxido-reductase, has previously been shown to be correlated with enhanced transmissibility in vivo. In sum, our findings unveiled several features underpinning the success of a locally-evolved L4.3/LAM clonal complex, lending further support to the critical role of genes encoded by the ESX/type VII secretion system.